Biogeography of soil microbial habitats across France - Battle Karimi; Jean Villerd; Samuel Dequiedt; Sébastien Terrat; Nicolas Chemidlin‐Prévost Bouré; Christophe Djemiel; Mélanie Lelièvre; Julie Tripied; Virginie Nowak; Nicolas P. A. Saby; Antonio Bispo; Claudy Jolivet; et al. (Global Ecology and Biogeography, 2020)
Aim Intensive studies since the beginning of the 21st century have provided vast amounts of knowledge about soil microbial diversity at local and global scales. However, microbial habitats have been poorly investigated at large scale. This study aims to characterize soil bacterial habitats across France for the first time by integrating the description of numerous environmental factors and human activities. Location We focus on the large spatial scale of mainland France using the largest spatially explicit soil sampling set available across France (2,173 soils, area = 5.5 × 10 5 km 2 ). Major taxa studied Soil bacteria and archaea were studied by a high throughput sequencing approach targeting the V3‐V4 region of the 16S ribosomal ribonucleic acid ( rRNA ) gene directly amplified from soil DNA. Methods We applied decision tree learning and geostatistical approaches combining the abundant data on soil microbes and large‐scale environmental description in order to conduct a comprehensive analysis of soil bacterial and archaeal communities. Results We identified a complex mosaic of 16 distinct terrestrial habitats, based on soil type and management (pH, C : N ratio, land use). As for plants and animals, each habitat hosted generalist and specialist taxa and a specific interaction network directly or indirectly impacted by human activities. Main conclusions In a context of global change, our results emphasize that the policies for biodiversity and habitat conservation should now integrate soil microorganisms conceptually and technically.